Mapping Breast Cancer Microenvironment Through Single-Cell Omics - Tan, Zhenya; Kan, Chen; Sun, Minqiong; Yang, Fan; Wong, Mandy; Wang, Siying; Zheng, Hong (Frontiers in Immunology, 2022)
Breast cancer development and progression relies on not only the proliferation of neoplastic cells, but also the significant heterogeneity in the surrounding stroma or tumor microenvironment. Its unique immune microenvironment, including tumor infiltrating lymphocytes, complex myeloid cells, lipid-associated macrophages, cancer-associated fibroblasts (CAFs), and other molecules that promote the growth and migration of tumor cells, has been shown to play a crucial role in the occurrence, growth, and metastasis of Breast cancer. However, a detailed understanding of the complex microenvironment in breast cancer remains largely unknown. The unique pattern of breast cancer microenvironment cells has been poorly studied, neither has the supportive role of these cells in pathogenesis been assessed. Single-cell multi-omics biotechnology, especially single-cell RNA sequencing (scRNA-seq) reveals single-cell expression levels at much higher resolution, finely dissecting the molecular characteristics of tumor microenvironment. Here, we review the recent literature on breast cancer microenvironment, focusing on scRNA-seq studies and analyzing heterogeneity and spatial location of different cells, including T and B cells, macrophages/monocytes, neutrophils and stromal cells. This review aims to provide a more comprehensive perception of breast cancer microenvironment and annotation for their clinical classification, diagnosis and treatment. Furthermore, we discuss the impact of novel single cell omics technologies, such as abundant omics exploration strategies, multi-omics conjoint analysis mode and deep learning network architecture, on the future research of breast cancer immune microenvironment.